2009
DOI: 10.1021/ed086p630
|View full text |Cite
|
Sign up to set email alerts
|

What Teaching Teaches: Mentoring and the Performance Gains of Mentors

Abstract: A peer mentoring program was added to an introductory chemistry course at a large university. The introductory chemistry course prepares students with little or no previous chemistry background to enter the main-stream general chemistry sequence and is part lecture and part small-group problem-solving. Faculty instructors are responsible for the lecture while peer mentors handle the group problem-solving portion. Peer mentors, recruited from previous introductory chemistry course, are chosen for their knowledg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 17 publications
3
60
0
1
Order By: Relevance
“…The reviewed research extends prior knowledge regarding potential benefits of mentoring for both the protégé (student) and mentor (Amaral & Vala, 2009;Campbell, Smith, Dugan, & Komives, 2012), sensemaking of the mentoring relationship and associated experiences (Griffin, 2013;Luna & Prieto, 2009), and mentoring as related to civic outcomes such as social responsibility and socially responsive leadership (Haddock et al, 2013). Qualitative findings also add to knowledge regarding the mentee and mentor matching process, students' and mentors' expectations for mentoring relationships, and what mentoring looks like in the context of particular disciplines and programs.…”
Section: Synthesis Of Key Findingsmentioning
confidence: 66%
See 1 more Smart Citation
“…The reviewed research extends prior knowledge regarding potential benefits of mentoring for both the protégé (student) and mentor (Amaral & Vala, 2009;Campbell, Smith, Dugan, & Komives, 2012), sensemaking of the mentoring relationship and associated experiences (Griffin, 2013;Luna & Prieto, 2009), and mentoring as related to civic outcomes such as social responsibility and socially responsive leadership (Haddock et al, 2013). Qualitative findings also add to knowledge regarding the mentee and mentor matching process, students' and mentors' expectations for mentoring relationships, and what mentoring looks like in the context of particular disciplines and programs.…”
Section: Synthesis Of Key Findingsmentioning
confidence: 66%
“…For example, research by Amaral and Vala (2009) suggested that peer mentors may directly benefit from mentoring. The researchers found that peer mentors earned higher grades and enrolled in more courses compared to students who had not participated as peer mentors.…”
Section: Mentoring Benefitsmentioning
confidence: 99%
“…According to Amaral and Vala (2009), who perform the PLTL model in the first year general chemistry course at the undergraduate level, examine the effects of the model on mentor students' (peer leaders) successes and their retention. The performances of students who attend and do not attend the mentoring program (training) were compared.…”
Section: Pltl Implementations In General Chemistry Coursementioning
confidence: 99%
“…McCreary, Golde, and Koeske (2006) implement PLTL model in the laboratory of the general chemistry course with experimental and control groups and examine the impact of the model. Both from the content analysis of students' written exam responses and other qualitative data, they conclude that students in PLTL workshops have a higher performance than the other groups.According to Amaral and Vala (2009), who perform the PLTL model in the first year general chemistry course at the undergraduate level, examine the effects of the model on mentor students' (peer leaders) successes and their retention. The performances of students who attend and do not attend the mentoring program (training) were compared.…”
mentioning
confidence: 99%
“…Over time, and with effective assistance of a more experienced member of the community (e.g., a UTA), they will develop an increasing sense of identity as a master practitioner (Lave & Wenger, 1991 These three theories connect a) the skills needed from the UTA to assist their less experienced peers in learning, b) the relationship between UTA and student that can help acculturate the student into the community of practice, and c) the students' need for an effective proxy to predict success in a course of study. (Amaral & Vala, 2009;Gosser & Roth, 1998;House & Wohlt, 1990;Hug, Thiry, & Tedford, 2011;Lewis, 2011 (Johnson, Johnson, & Smith, 1998) and problem-solving groups, questioning strategies, metacognitive activities, and formative assessment approaches that inform future instruction. One of the CHEM 201 professors also participated in the learning strategies instruction, presenting some topics and listening in on UTA small group conversations.…”
Section: Lave and Wenger's Situated Learning Theorymentioning
confidence: 99%